PENERAPAN TEKNOLOGI BERDASARKAN LUAS LAHAN DAN PENGARUHNYA TERHADAP PRODUKTIVITAS, DAN EFISIENSI USAHATANI KENTANG (Solanum tuberosum, L) (Suatu Kasus Pada Petani Kentang di Kecamatan Cipanas, Kabupaten Cianjur, Jawa Barat) - Lukman Lukman; Euis Dasipah; Karyana KS (Universitas Galuh, 2022)
This study was to determine the effect of land area on the application of productivity technology and efficiency of granola potato farming. The unit of analysis is farmers who plant granola potatoes in MT 2021 in Cipanas District, Cianjur Regency, West Java. Respondents were taken from sample farmers with a layered random technique comparable to the size of 55 people. The analysis technique and hypothesis testing used were Kruskal Wallis and Cgi Square analysis. The results showed that potato farming performance based on land area: wide (1.75 ha), moderate (0.65 ha); and narrow (0.36 ha) shows relatively diverse conditions. The productivity of each farm land reached 13.56 tons/ha; 11.25 tons/ha; and 11.05 tons/ha. The income achievement of potato farming is Rp. 61,564,317/ha, medium land is Rp. 38.986.882/ha, and narrow land is Rp. 38.196.880/ha. R/C farming efficiency respectively: 2.34; 1.87 and 1.79. There are differences in the application of technology in potato farming based on large, medium, and narrow land areas. Potato farmers with large plots showed a better level of technology application than potato farmers with medium or narrow plots. The level of achievement of the application of potato farming technology was obtained by farmers with an area of 83.99% very good criteria; medium land farmers 72.50% good criteria; and farmers with narrow land 71.73 good criteria. There is a positive effect of the application of technology on the achievement of potato farming productivity. The productivity of large land farming shows a higher level than potato farmers with medium or narrow land. Each obtained by farmers with an area of 13,560 kg/ha; medium land farmers 11,185 kg/ha; and small land farmers 11,021 kg/ha. There is a positive effect of the application of technology on the efficiency of potato farming. Farming efficiency of farmers with large land shows a higher level than farmers with medium or narrow land. Each obtained by farmers with an area of 2.34; medium land farmers 1.87; and farmers with narrow land 1.79.